“Effectiveness of Video Assisted Teaching Programme On Knowledge Regarding Premenstrual Syndrome Among Adolescent Girls Studying at Akkamahadevi Women’s Arts, Science and Commerce College at Bagalkot. - Chatter, Aishwarya A; Itti, Jayashri G; Patil , Kavita (International Journal of Membrane Science and Technology, 2023)
Background: Adolescent stage is very important in the life of a girl, because in this stage physical, sexual and psychological maturity takes place. The major landmark of puberty for females is menarche, the onset of menstruation, which occurs on an average between ages 12 and 13. The start of menstruation is usually a mixture of excitement and anxiety. Aims: To assess the effectiveness of video assisted teaching programme on knowledge regarding premenstrual syndrome among adolescent girls studying at akkamahadevi women’s arts, science and commerce college at Bagalkot.Settings and Design: This Experimental study included a sample of 100 adolescent girls. 50 adolescent girls for experimental group had received Video assisted teaching programme at akkamahadevi women’s arts, science and commerce college at Bagalkot.Methods and Material: Data were collected using Structured Interview schedule method. Tools used for data collection were; socio-demographic questionnaire and Structured knowledge questionnaire.Results: Result depicts that an administration of Video assisted teaching programme to the experimental group has increased (16.55 %) their knowledge regarding Premenstrual syndrome as compared with control group.Result showed that there is a statistically significant difference between pre-test and post –test knowledge scores regarding premenstrual syndrome among adolescent girls of both experimental (t=-15.13 (tab, p< 0.0001) and control group (t=-2.187, p< 0.05) adolescent girls.A statistically significant difference was found between post- test knowledge scores regarding premenstrual syndrome of experimental group and control group adolescent girls [t=10.166, p<0.0001].There was no significant association was found between knowledge scores regarding premenstrual syndrome among adolescent girls of experimental group with any of their selected socio-demographic variables. There is a significant association between area of residence (?2==4.675, P<0.05) between knowledge scores regarding premenstrual syndrome and there was no significant association found between knowledge scores regarding premenstrual syndrome among adolescent girls of control group with any of their remained selected socio-demographic variables.